(untitled) (Journal of the College of Basic Education, 2025)
The research investigates how the Pentagram Strategy shapes eighth-grade students’ learning of scientific material along with their intellectual motivation abilities. A research sample of 65 students was selected purposefully from the study population located in Duhok City for academic year 2024-2025. A selection process divided participants into two similar groups which considered attributes including their age range alongside IQ levels and previous science grades and academic achievements together with their parents’ education status. Instructors delivered Pentagram Strategy instruction to the experimental group yet taught the control group through conventional teaching methods. For research objectives verification and main and sub-hypothesis testing purposes the researchers constructed a 30-item conceptual test in its concluded form. A test was constructed to assess concept acquisition elements through definition-based questions and differentiation-based questions and application-based questions with 30 multiple-choice and matching questions across each element. The assessment underwent validation procedures that measured its reliability as well as consistency and psychometric properties. The research team produced educational plans for experimental and control groups before science teachers carried out these curriculums in their respective schools. The experiment concluded when the first researcher conducted the conceptual test on participants before using proper statistical methods to analyze data. The study results showed two major statistical relationships: (1) the experimental group utilizing the Pentagram Strategy achieved better scientific concept acquisition than the control group and (2) intellectual motivation development achieved better results in the experimental group. The study’s outcome guided researchers to draw conclusions and give recommendations with proposed ideas about future research.